細胞에 對한 韓醫學的 比較硏究 - Yu Byeong Wan(柳秉完); Hwang Woo Jun(黃祐準); Lee Si Hyeong(李始炯); Keum Kyeong Soo(琴坰樹) (대한한의학원전학회지, 2006)
A comparative study of the Oriental Medicine on the cell Dept. of Oriental Medicine Classics, Won Kang University Yu Byeong WanㆍHwang Woo JunㆍLee Si HyeongㆍKeum Kyeong Soo A study of scientific methods in a study of comparative on the oriental medicine and the western medicine evidence to find on the cause-effect relationship. The rationality in a study of process and the confidence in a study of result were improved by a study of methods on the cause-effect relationship . Also a comparative study on the Jeong(精) of the oriental medicine and the cell of the western medicine, after established a model of the cause-effect relationship secured a suitability of a comparative subject and operationalization of a comparative variable to the rationality in a study of process. The Jeong(精) and the cell are the character of a unit and the character of a matter on the human body. The Jeong(精) and the cell are a point of similarity in the function. The Jeong(精) and the cell are a relation in the mechanism. Our paper reviewed a study of comparative methods on the oriental medicine and the western medicine, and suggest an identic interpretation on the human body. KCI Citation Count: 0